2012
DOI: 10.1037/a0026491
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism in African American students: Relationship to racial identity, GPA, self-esteem, and depression.

Abstract: This study examined 219 African American college students at predominantly White universities using the constructs of perfectionism, academic achievement, self-esteem, depression, and racial identity. Cluster analysis was performed using the Almost Perfect Scale-Revised (APS-R), which yielded three clusters that represented adaptive perfectionists, maladaptive perfectionists, and nonperfectionists. These three groups were compared on their scores on the Rosenberg Self-Esteem Scale (RSES), the Center for Epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 65 publications
3
35
1
2
Order By: Relevance
“…Researchers who have used measures based on Cross's model (and derivative models) have predicted that individuals with more advanced racial identities would also have higher scores on a given academic achievement measure (Elion, Wang, Slaney, & French, 2012) based on the argument that racism on college campuses derives from college drop-out rates or poor academic performance among Black students. It is believed that when individuals have positive racial attitudes about their own race, they are able to focus on school without stressful distractions.…”
Section: Cross's Modelmentioning
confidence: 99%
“…Researchers who have used measures based on Cross's model (and derivative models) have predicted that individuals with more advanced racial identities would also have higher scores on a given academic achievement measure (Elion, Wang, Slaney, & French, 2012) based on the argument that racism on college campuses derives from college drop-out rates or poor academic performance among Black students. It is believed that when individuals have positive racial attitudes about their own race, they are able to focus on school without stressful distractions.…”
Section: Cross's Modelmentioning
confidence: 99%
“…Moreover, those who have high examination anxiety usually have fewer study skills 43 . These factors lead to severe stress, depression, low self-confidence, and, finally, a decline in performance 44 . This problem is arguably more prominent in competitive high-level exams.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of college students, African-American students reported the highest levels of self-esteem compared with their peer groups, which can be partially attributed to their internalized self-images in the later stages of their educational careers. 20 African-American students who achieved a college education had higher levels of self-esteem compared to their peers who did not go to college. There is ample evidence that as an ethnic group, Asians are modest when responding to surveys assessing self-efficacy.…”
Section: Discussionmentioning
confidence: 99%